Highly Efficient Guanidinium‐Based Quasi 2D Perovskite Solar Cells via a Two‐Step Post‐Treatment Process. Issue 11 (23rd July 2019) - Zhang, Yingzhu; Chen, Jiehuan; Lian, Xiaomei; Qin, Minchao; Li, Jun; Andersen, Thomas Rieks; Lu, Xinhui; Wu, Gang; Li, Hanying; Chen, Hongzheng
Abstract: 2D perovskites with alternating cations in the interlayer space (ACI) have raised increasing interest in the field of layered 2D perovskite solar cells (PVSCs). Herein, ACI quasi‐2D PVSCs with a chemical formula of C(NH2 )3 (CH3 NH3 )4 Pb4 I13 ( n = 4) are fabricated by an antisolvent method assisted by a novel two‐step post‐treatment process, in which guanidinium thiocyanate (GASCN) and MACl (GA = guanidinium, MA = methylammonium) are utilized as post‐treatment reagents, sequentially. With the first‐step post‐treatment by GASCN, the grain gaps within the perovskite films are dramatically diminished, leading to increased alignment and well‐ordered crystal grains. Consequently, the power conversion efficiency (PCE) of the corresponding devices increases by more than 50% (from 8.62% to 13.13%). After the second‐step post‐treatment by MACl, the trap states in the perovskite films are passivated, and as a result the PCE of the PVSCs is further enhanced to 15.27%. This work provides the new method of two‐step post‐treatment for fabrication of high quality 2D PVSC films. Abstract : A two‐step post‐treatment approach is applied to fabricate highly efficient quasi‐2D perovskite solar cells. In the first step, the segregated crystal grains are "glued" together, leading to a compact film with well‐ordered crystal grains. In the second step, the defect states in the perovskite films are passivated, resulting in an optimal PCE of 15.27%.